Determinants of the liability maturity of Polish companies - Mielcarz, Paweł; Osiichuk, Dmytro (Determinanty terminu zapadalności zobowiązań polskich przedsiębiorstw, 2016)
Using the firm-level panel data for Polish companies, we analyze the determinants of liability maturity with particular attention paid to the factors of financing constraints and information asymmetry. Consistent with prior research, we find that asset tangibility, liquidity, leverage and profitability significantly influence liability maturity choices. Additionally, we evidence that financing constraints may alter the impact of these factors. Companies identified as being financially constrained appear to have lower maturity of liabilities. Firms quoted on the main market of the Warsaw Stock Exchange are shown to hold a higher proportion of long-term liabilities compared to those quoted on New Connect, a stock exchange dedicated to young small cap companies. We also find that constrained status may determine firm’s financing decisions under crisis settings. Our empirical results show that companies experiencing financing constraints are likely to reduce liability maturity during a crisis, while their unconstrained counterparts may recur to additional long-term external financing in order to accommodate the repercussions of a trough. These findings contribute to the discussion of the financing constraints theory and shed light on some of the firms’ tactical financing decisions in an emerging economy
Nauki o Finansach = Financial Sciences, 2016, Nr 4 (29), s. 49-63
Keywords: liability maturity; financing constraints; emerging economy; termin zapadalności zobowiązań; ograniczenia kapitałowe; rynki wschodzące